Nano-analytical characterization of endogenous minerals in healthy placental tissue: mineral distribution, composition and ultrastructure. Issue 23 (8th October 2019) - Anthis, Alexandre H. C.; Tsolaki, Elena; Didierlaurent, Louis; Staubli, Samuel; Zboray, Robert; Neels, Antonia; Dietrich, Dörthe; Manser, Pius; Desbiolles, Lotus May; Leschka, Sebastian; Wildermuth, Simon; Lehner, Sandro; et al.
Abstract : This study reveals distinct characteristics of minerals formed during gestational ageing using nano-analytical characterization, and paves the way for the identification of markers for disease risks based on atypical placental mineral fingerprints. Abstract : Despite its crucial role, the placenta is the least understood human organ. Recent clinical studies indicate a direct association between placental calcification and maternal and offspring health. This study reveals distinct characteristics of minerals formed during gestational ageing using cutting-edge nano-analytical characterization and paves the way for investigations focused on the identification of potential markers for disease risks in a clinical setting based on atypical placental mineral fingerprints.